Introduction: What Does Racial Capitalism Have to Do With Cities and Communities?. (September 2022) - Dantzler, Prentiss; Korver-Glenn, Elizabeth; Howell, Junia
Social scientists have long debated whether racial inequality is an unfortunate consequence of political and economic exploitation or a core feature of capitalism. In 1983, Cedric Robinson synthesized these two opposing perspectives, calling the latter racial capitalism and demonstrating its theoretical viability. In recent years, scholars have increasingly employed Robinson's conception of racial capitalism to explain a wide array of phenomena. Yet, urban sociology has not fully explored how racial capitalism changes and reshapes our core theoretical approaches. To begin to fill this gap, this special issue presents original papers that employ racial capitalism to extend, challenge, or refine theories of and methods for understanding cities and communities. In this introduction, we outline urban scholars' historical explanations of racial inequality and provide an overview of the development and definition(s) of racial capitalism. We then summarize the papers included in this special issue and discuss a pathway forward for urban sociology.